Caroline Schlegel-Schelling: «Ero seduta qui a scrivere». Lettere - Fattorini, Vania (Biblioteca di Studi di Filologia Moderna, 2012)
The stars of the correspondence of Caroline Michaelis-Böhmer-Schlegel-Schelling (1763-1809), one of the most intriguing female figures in the German Romantic movement, are the relations with and between major exponents of the German scene of Enlightenment and Revolution, Classicism and Romanticism. Framed between an introduction dealing with Caroline herself and a detailed critical apparatus, Illuminismo e Rivoluzione, Classicismo e Romanticismo. Caroline Schlegel-Schelling: «Ero seduta qui a scrivere». Lettere proposes some of the most impassioned letters from her extensive correspondence in a document that is at once biographical, artistic, historical and literary. Fifty selected letters (plus an appendix with several letters she received from Friedrich Schlegel and Novalis), in a compilation that aims to cast light on the lively critical sensitivity combined with genuine literary talent that made Caroline the heart and soul of the Romanticism of Jena.